Self-Efficacy and Academic Performance in Colombian Dental Students. (2019)
Favorable self-efficacy beliefs have been theorized to predict better academic performance, but this association has been untested in dental education. To address this knowledge gap, the aim of this study was to determine the relationship between students' self-efficacy and academic performance in a Colombian dental school. This cross-sectional study was conducted in 2016 with dental students in all five years at the Universidad Cooperativa de Colombia, Pasto, Colombia. Prior to application for the measurement of self-efficacy, the psychometric properties of the Academic Behaviors Self-Efficacy Scale (ABSS) were examined using confirmatory factor analysis (CFA). Participants' semester grade point average was used as a measure of academic performance. Of the total 390 students, 320 participated (82% participation rate). A three-factor model for ABSS with the dimensions of communication, attention, and excellence emerged from the CFA, demonstrating optimal fit indices: ? 2 S-B =468.912; p0.01; NNFI=0.994; CFI=0.996; RMSEA=0.031 (90% CI 0.021, 0.037); SRMR=0.070; AIC=344.912. Self-efficacy was positively associated with academic performance (rho=0.259; p0.001). This association was statistically significant only among women (rho=0.361; p0.001) and those in low SES strata (1-2: rho=0.310; p0.001) and was highest among students with a heavy (15 credits) academic course load (rho=0.306; p=0.001). The ABSS demonstrated adequate psychometric properties. Academic self-efficacy was positively associated with academic performance, and this association was most pronounced among women students, those in low SES strata, and those taking a heavy course load.